Needs Analysis about Female Students’ Interest and Anxiety for the Development of the Science Module - Tukur Muhammad; Lucy Aja; Shakiro Joyce (Journal of Research in Education and Pedagogy, 2025)
Science is still the best way for a country to advance technologically in the modern world, and women have been engaged in scientific endeavors for decades. Therefore, it has been widely acknowledged that enhancing science education and providing female children with job opportunities is essential for national growth. However, gender inequality against female students in science classes has been acknowledged in Nigeria. This issue is caused by parental views, religious beliefs, cultural influences, and female students’ lack of interest and anxiety in science classes, which has led to a decline in the number of girls enrolled in secondary schools in Nigeria. Therefore, this study investigated the problems in science curricula and textbooks as well as the reasons for female students’ lack of interest in and worry about learning science. A checklist of questions about interest in and worry about learning science was used to examine the scientific curricula and texts. Focus groups with particular SS II female students were also held utilizing the interview methodology. The results showed that problems with the Nigerian scientific textbooks and curriculum contribute to the uninteresting nature of science instruction. However, the focus group interview results show that female students face obstacles that make them less enthusiastic and nervous about studying science in secondary school. This led to the determination that a teaching module incorporating factors related to interest and anxiety in science learning was necessary.